The Economy of Developing Countries in the Context of Globalization: Global Supply Chain Management - Svetlana Glushkova; Oksana Lomakina; Tatyana Sakulyeva (International Journal of Supply Chain Management, 2019)
Globalization has a great influence on the development of the independent state economies. Supply chain management (SCM) in the era of expanding global sourcing can play a critical role in diffusing corporate responsible practices throughout the emerging developing countries economies. Thus, this paper aims to examine how responsible SCM can contribute to supplier performance, including environmental, social and operational performances through the improvement of relationship commitment in the Asian context. The research deals with the economic aspect of globalization and analyzes the indicators that most closely reflect the development of countries in the globalizing world economy inward foreign direct investment, outward foreign direct investment, economic globalization index and the dependence of a country's GDP on foreign direct investment. It is assumed that foreign direct investment has a significant impact on the development of the country's economy. To check this hypothesis, the relationship between the growth of the gross domestic product of Asian countries and foreign direct investment is being investigated. The calculated correlation coefficient between the growth rates of the country's GDP and the growth rates of foreign direct investment did not show a relationship between these variables. Using the matrix to analyze Asian countries from the standpoint of inward foreign direct investment and the economic globalization index, it was determined that China and Singapore are the countries with high levels of inward FDI and high rates of economic globalization. The coefficient of economic globalization of such countries as Japan, Indonesia, Kazakhstan, Thailand, Malaysia, the Republic of Korea, India, Vietnam and Kyrgyzstan is above 50 out of 100. However, foreign direct investment in these countries is much lower than in China.